2014
DOI: 10.1001/virtualmentor.2014.16.06.msoc1-1406
|View full text |Cite
|
Sign up to set email alerts
|

Race: A Starting Place

Abstract: Health status, access to and quality of care, and numerous social factors associated with health vary across racial groups [1,2]. Many applaud the collection and use of race data to identify and monitor progress in addressing health disparities [3][4][5][6]. The National Institutes of Health (NIH) requires and the Food and Drug Administration (FDA) recommends the collection of race data in clinical research [7,8]; the 2009 Health Information Technology for Economic and Clinical Health (HITECH) Act provided fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…For example, dating as far back as the antebellum period, physicians attributed poor health among slaves to their biological inferiority, rather than to their conditions of servitude. 5 Such beliefs persist today. In April 2016, a study found that 50% of white medical students and residents hold false beliefs about biological differences between black and white people (e.g., black people's skin is thicker; black people's blood coagulates more quickly).…”
Section: Understand How Racism Has Shaped the Disparities Narrativementioning
confidence: 99%
See 2 more Smart Citations
“…For example, dating as far back as the antebellum period, physicians attributed poor health among slaves to their biological inferiority, rather than to their conditions of servitude. 5 Such beliefs persist today. In April 2016, a study found that 50% of white medical students and residents hold false beliefs about biological differences between black and white people (e.g., black people's skin is thicker; black people's blood coagulates more quickly).…”
Section: Understand How Racism Has Shaped the Disparities Narrativementioning
confidence: 99%
“…4 In the US, this was carried out through centuries of slavery premised on the social construct of race. 5 In a very literal sense, this country codified the value of black lives as 3/5 that of whites in the Constitution. Historical notions about race have shaped our scientific research and clinical practice.…”
Section: Learn Understand and Accept America's Racist Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…reflected a common belief that "white blood" could be tainted by "black blood" due to hypodescent practice (Root, 1992). The U.S. government eventually granted privileges to low-status people considered white and continued to withhold them from people considered black, racial classification had real consequences and membership in racial groups became increasingly important to identity (Cunningham, 2014). The U.S. government has collected data on race or color since its first census in the year 1790 (U.S. Census Bureau, 2002).…”
Section: Perfidious Racial Hierarchymentioning
confidence: 99%
“… 18 , 19 In the United States, it has been used since the 17th century to subdivide humans from one another phenotypically. 20 , 21 However, race is a fluid construct; a person's racial identity can change over time and self-ascribed race can differ from assigned race. 22 Contrastingly, ethnicity, used as a sociocultural construct, 9 , 16 often refers to shared cultural identification, religion, and language.…”
Section: Introductionmentioning
confidence: 99%